Pendampingan Digital Marketing bagi Pengrajin Batik guna Meningkatkan Branding Batik di Tanjungbumi - Hasanah, Uswatun; Awwalia, Luthfi; Arnani, Ni Putu Rizky (LPPM Universitas Trunojoyo Madura, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's national economic development. One sector with significant development potential is the batik industry, particularly handwritten batik (batik tulis) found in Tanjungbumi, Bangkalan, Madura. However, many batik artisans continue to rely on traditional sales methods, which restrict their market reach. This community service activity aims to enhance the branding and digital marketing capabilities of batik artisans through training on utilizing social media as a promotional tool. The implementation method consists of three stages: preparation, coordination, and educational activities. The training focuses on optimizing social media platforms, creating engaging content, and effectively using hashtags. Risk mitigation topics, such as adding watermarks to content, were also introduced to prevent unauthorized copying of batik patterns. The results indicate an improved understanding among artisans regarding the significance of branding and digital marketing strategies. The participants expressed great enthusiasm and were motivated to apply the knowledge gained. This activity demonstrates that support from higher education institutions can encourage artisans to adapt to technological advancements and enhance their product competitiveness. A recommendation arising from this activity is the need for ongoing support and advanced digital training to ensure batik artisans are better prepared to compete in the digital era.